2020
DOI: 10.1186/s13071-020-04104-3
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic efficacy of Schistosoma japonicum cystatin on sepsis-induced cardiomyopathy in a mouse model

Abstract: Background: Myocardial dysfunction is one of the most common complications of multiple organ failure in septic shock and significantly increases mortality in patients with sepsis. Although many studies having confirmed that helminthderived proteins have strong immunomodulatory functions and could treat inflammatory diseases, there is no report on the therapeutic effect of Schistosoma japonicum-produced cystatin (Sj-Cys) on sepsis-induced cardiac dysfunction. Methods: A model of sepsis-induced myocardial injury… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 73 publications
5
16
0
Order By: Relevance
“…After being treated with Ts -AES, protein expression levels and the mRNA expression levels of HMGB1, TLR2 and MyD88 in lung tissues were significantly decreased. Our results further confirm that severe infection of bacteria in sepsis stimulates inflammatory immune responses through HMGB1/TLR2/MyD88 activation signal pathway as shown for other helminth-derived proteins ( Li et al., 2017 ; Ilic et al., 2018 ; Gao et al., 2020 ).…”
Section: Discussionsupporting
confidence: 86%
“…After being treated with Ts -AES, protein expression levels and the mRNA expression levels of HMGB1, TLR2 and MyD88 in lung tissues were significantly decreased. Our results further confirm that severe infection of bacteria in sepsis stimulates inflammatory immune responses through HMGB1/TLR2/MyD88 activation signal pathway as shown for other helminth-derived proteins ( Li et al., 2017 ; Ilic et al., 2018 ; Gao et al., 2020 ).…”
Section: Discussionsupporting
confidence: 86%
“…The same team showed that in a murine model of LPS-induced sepsis, intraperitoneal administration of rSj-Cys significantly alleviated LPS-induced organ pathologies, reduced the levels of liver and renal functional indexes and pro-inflammatory cytokines, and increased the serum level of IL-10 ( 55 ). The same group showed that rSj-Cys significantly reduced sepsis-induced cardiomyopathy in mice and suggested this molecule should be considered as a potential therapeutic for preventing and treating sepsis-associated cardiac dysfunction ( 117 ).…”
Section: Therapeutic Potential Of Live Schistosome Infection and Schimentioning
confidence: 99%
“…Our previous studies have identified that treatment with Sj -Cys significantly reduced the pathology caused by LPS-induced ( Wan et al., 2018 ) or bacterial infestation-induced ( Li et al., 2017 ) sepsis in mice with less inflammation and tissue damage through stimulating anti-inflammatory cytokines and inhibiting Th1 pro-inflammatory cytokines. In particular, treatment with Sj -Cys significantly reduced sepsis-induced cardiomyopathy ( Gao et al., 2020 ). However, the immunological mechanism and targeted immune cells underlying the immunomodulation and therapeutic effect of Sj -Cys on sepsis remains unknown.…”
Section: Introductionmentioning
confidence: 99%